TH6.13 Post-Operative Pain Management Following Emergency Laparotomy. (9th August 2022) - Shepherd, Thomas; Butterworth, James; Islam, Rafiza; Asante, Kirsty; Oke, Olatokunbo
Abstract: Aims: Post-operative pain is a common yet challenging presentation. Although an expected part of the acute recovery phase, uncontrolled pain is associated with poorer patient experience, delayed functional recovery and increased morbidity. Up to 40% of patients report severe pain that negatively impacts on their post-operative recovery. We aimed to determine whether post-operative complications and length of hospital admission were associated with choice of analgesic agents. Methods: We conducted a retrospective observational study of 42 patients who underwent a laparotomy between March – May 2021. Data was extracted from patients electronic medical records and summarised in Microsoft Excel. Statistical analysis was performed using the Chi-Squared and Mann-Whitney U tests. Results: 22 patients (52.4%) experienced post-operative complications whilst 20 (47.6%) did not. In those without post-operative complications, a greater proportion received Patient Controlled Analgesia (PCA) compared to those with post-operative complications (17, 85% vs 11, 50%, p = 0.02). We also observed a trend towards greater use of Oxycodone (11, 55% vs 6, 27%) and Meptazinol (11, 55% vs 7, 32%) in those without post-operative complications (p= 0.07 and p = 0.13 respectively). The length of hospital admission was significantly shorter for patients who received PCA (median = 11 days) compared to those who did not (median = 15 days) (U = 111.5, p = 0.04). Conclusions: This study emphasises the importance of effective post-operative analgesia in reducing post-operative complications and improving speed of recovery. We suggest that the use of PCA should be encouraged for post-operative analgesia following emergency laparotomies.